The Perceived Problems and Help-Seeking Preferences of Chinese Immigrants in Montreal - Christensen, Carole Pigler (Canadian Journal of Counselling and Psychotherapy, 2011)
Helping professionals have long recognized the underuse of mainstream services by immigrants of Chinese origin. Although popular belief suggests that they experience few problems for which they would tend to seek help outside of the family, little empirical evidence exists to either support or negate this assumption. This exploratory descriptive study examines the nature and frequency of problems and help-seeking preferences of a random sample of 60 men and women of Chinese origin. Results confirm that the family was the preferred first choice of help for most psychological and interpersonal problems, friends being a frequent second choice of female respondents. No overall significant differences are found between males and females when choices for help were examined. These findings are discussed in terms of policy and practice implications, and the need for further research.